Key houses of the twentieth century : plans, sections and elevations. - Davies, Colin, 1929- (London : Laurence King, 2006)
Featuring over 100 of the most significant and influential houses of the twentieth century, this book includes classic works by such seminal architects as Le Corbusier, Frank Lloyd Wright, Mies van der Rohe and Alvar Aalto, as well as those by more recent masters, such as Tadao Ando, Rem Koolhaas and Glen Murcutt. For each of the houses included there are numerous, accurate scale plans showing each floor, together with elevations, sections and site plans where appropriate. All of these have been specially drawn for this book and are based on the most up-to-date information and sources. There is also a concise text explaining the significant architectural features of the building and the influences it shows or generated, together with colour images. Cross-references to other buildings in the book highlight the various connections between these key houses. The quality and number of the line drawings, together with the authoritative text and images, allow all the buildings to be understood in detail.
CDROM bevat alle tekeningen
Keywords: Bouwkunde